Valoração de tecnologias e empresas formadas a partir de novas tecnologias - Henrique Mendes Silva (2008)
Technology innovation is pointed out as a strong tendency for the 21th century, since it can be a key variable to regional economic development. Most of the young technology companies face high uncertainty levels. They have an interesting idea but no commercial product yet. This dissertation considers the problem of valuating technology projects and startup firms created from new technologies in the early stagesof its creation. We propose a dynamic programming model which takes into account both Real Options and Discounted Cash Flow methodologies. In other words, our model has a hybrid approach. In addition, we discuss the models practical implementation through an empirical example. The results show the model considers the technology potential of becoming a product platform and both exogenous (market) and endogenous (technical) uncertainties. The model can also support negotiations between entrepreneurs and investors.